MOTIVASI KERJA PETUGAS KEBERSIHAN (CLEANING SERVICE) DI LINGKUNGAN KAMPUS BINA WIDYA UNIVERSITAS RIAU KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Utami, Melisa; Maemunaty, Titi; Wilson, Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to determine (1) intrinsic work motivation that causes cleaning service work motivation in the cleaning environment of Bina Widya campus, Riau University, Simpang Baru Village, Tampan District, Pekanbaru City, (2) Extrinsic work motivation which causes work motivation cleaning (cleaning service) in the Bina Widya campus environment, Riau University, Simpang Baru Village, Tampan District, Pekanbaru City, (3) The most dominant work motivation between intrinsic work motivation and extrinsic work motivation which causes the cleaning service work motivation in the Bina Widya campus environment Riau University, Simpang Baru Village, Tampan District, Pekanbaru City. The sample in this study amounted to 47 people, namely cleaning service in the Bina Widya campus environment, Riau University, Simpang Baru Village, Tampan District, Pekanbaru City with simple random sampling technique. Data collection techniques using a questionnaire. Data analysis techniques using the SPSS program and percentage calculations. The results of this study indicate that intrinsic work motivation that causes cleaning service work motivation (cleaning service) in the Bina Widya campus environment, Riau University, Simpang Baru Subdistrict, Tampan District, Pekanbaru City, in terms of performance, appreciation, responsibility and development are relatively high and Extrinsic work motivation causes motivation cleaning service work in the Bina Widya campus environment, Riau University, Simpang Baru Village, Tampan District, Pekanbaru City, in terms of salary/income, working conditions, relationships between people, and high social status.Key Words: Motivation, Work, Work Motivation, Cleaning Service